Lessons from a simultaneous LEAN and BIM implementation in a residential pilot project in Colombia (2018)
Construction projects are afflicted by cost and time overruns, primarily due to inadequate information sharing between project participants that causes productivity reductions in the AEC industry. Colombia faces an opportunity to increase construction productivity by 5 to 7 times by working on different areas of its value chain. Building Information Modeling (BIM) emerged as a digital platform through which project teams can share and manage information better. Lean construction practices address the issue of improving coordination within a project team, smoothing workflow in construction projects through features that reduce waste and increase value. The present research is an applied study that comprises the analysis of the integration of Lean practices and BIM tools through a real-life implementation in a residential project. This paper contributes to knowledge on BIM and Lean adoption by showing how lean practices reduce coordination-related issues within the project construction and BIM adoption makes the benefits of Lean principles visible. Additionally, the literature still lacks specific examples of client's simultaneous implementation of BIM and Lean for the first time in medium-sized construction companies. The final purpose is to report experiences, opportunities for improvement and lessons learned from the implementation. Findings suggest that BIM in combination with applied lean principles can be implemented on construction projects to improve project performance.